Tick Cell Lines in Research on Tick Control - Al-Rofaai, Ahmed; Bell-Sakyi, Lesley (Frontiers in Physiology, 2020)
Ticks and the diseases they transmit are of huge veterinary, medical and economic importance worldwide. Control of ticks attacking livestock and companion animals is achieved primarily by application of chemical or plant-based acaricides. However, ticks can rapidly develop resistance to any new product brought onto the market, necessitating an ongoing search for novel active compounds and alternative approaches to tick control. Many aspects of tick and tick-borne pathogen research have been facilitated by the application of continuous cell lines derived from some of the most economically important tick species. These include cell lines derived from acaricide-susceptible and resistant ticks, cell sub-lines with in vitro-generated acaricide resistance, and genetically-modified tick cells. Although not a replacement for the whole organism, tick cell lines enable studies at the cellular and molecular level and provide a more accessible, more ethical and less expensive in vitro alternative to in vivo tick feeding experiments. Here we review the role played by tick cell lines in studies on acaricide resistance, mode-of-action of acaricides, identification of potential novel control targets through better understanding of tick metabolism, and anti-tick vaccine development, that may lead to new approaches to control ticks and tick-borne diseases.